Determinants of household direct and indirect costs: an insight for health-seeking behaviour in Burkina Faso - Tin, Tin Su; Flessa, Steffen (Springer Verlag, 2013)
The objective of the study is to identify the determinants of household direct and indirect costs in the Nouna District, Burkina Faso. The data used were from a household survey conducted during 2000-2001. The multinominal logit models were applied to investigate the determinants of direct and indirect costs. The respondents who were sick in the rainy season and severity of illness significantly increased the probability of having high direct and indirect household costs. Acute illness occured in an adult was positively associated with magnitude of household indirect costs. Household economic status and utilization of western medical care played an important role in magnitude of direct cost. The information on determinants of household direct and indirect costs is necessary in order to get a complete picture of household costs for seeking health care and identification of vulnerable social groups and households.